Mutation update of transcription factor genes FOXE3, HSF4, MAF, and PITX3 causing cataracts and other developmental ocular defects. Issue 4 (16th January 2018) - Anand, Deepti; Agrawal, Smriti A.; Slavotinek, Anne; Lachke, Salil A.
Abstract: Mutations in the transcription factor genes FOXE3, HSF4, MAF, and PITX3 cause congenital lens defects including cataracts that may be accompanied by defects in other components of the eye or in nonocular tissues. We comprehensively describe here all the variants in FOXE3, HSF4, MAF, and PITX3 genes linked to human developmental defects. A total of 52 variants for FOXE3, 18 variants for HSF4, 20 variants for MAF, and 19 variants for PITX3 identified so far in isolated cases or within families are documented. This effort reveals FOXE3, HSF4, MAF, and PITX3 to have 33, 16, 18, and 7 unique causal mutations, respectively. Loss‐of‐function mutant animals for these genes have served to model the pathobiology of the associated human defects, and we discuss the currently known molecular function of these genes, particularly with emphasis on their role in ocular development. Finally, we make the detailed FOXE3, HSF4, MAF, and PITX3 variant information available in the Leiden Online Variation Database (LOVD) platform athttps://www.LOVD.nl/FOXE3, https://www.LOVD.nl/HSF4, https://www.LOVD.nl/MAF, andhttps://www.LOVD.nl/PITX3 . Thus, this article informs on key variants in transcription factor genes linked to cataract, aphakia, corneal opacity, glaucoma, microcornea, microphthalmia, anterior segment mesenchymal dysgenesis, and Ayme‐Gripp syndrome, and facilitates their access through Web‐based databases. Abstract : We provide a Mutation Update for the transcription factors FOXE3, HSF4, MAF and PITX3 that are necessary for development of the ocular lens and whose variants are commonly linked to congenital cataract, among other defects. As illustrated, of the 33 unique FOXE3 mutations, 15 present in the forkhead domain are missense variants, predicted as damaging or experimentally validated as nonfunctional proteins. Interestingly, specific mutations in the forkhead DNA‐binding domain have specific outcomes with regard to either ocular or aortic defects.